PENGGUNAAN SYSTEMATIC APPROACH TO PROBLEM SOLVING UNTUK MENINGKATKAN KEMAMPUAN SISWA MENYELESAIKAN SOAL GLBB - Irma, Liasa; Djudin, Tomo; B. Arsyid, Syaiful (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis study aims to know the effectiveness of the use of systematic approach to problem solving to improve students' ability to solve the accelerated uniform motion in SMA Negeri 1 Sungai Ambawang. The research method used was Pre-Experimental Design with the design of One-Group Pretest Posttest Design. The sample of this study involved 24 MIA 1 class X students who were selected using Intact Group Random Sampling. The test used in this study is a limited description of 4 questions given before and after treatment. The results of the study found: (1) the average score of the students 'abilities before and after completing the questions was 13.33 and 36.42; (2) there were differences in students' ability to solve accelerated uniform motion before and after being taught using systematic approach to problem solving (p <0.05); (3) the effectiveness of using systematic approach to problem solving to improve students' ability to solve accelerated uniform motion is relatively high (ES = 3.41). This research is expected to be used as an alternative to improve students' ability to solve problems.Â Keyword: Ability, SAPS, and Accelerated Uniform Motion